2018
DOI: 10.1016/j.fertnstert.2018.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and insulin resistance in mothers, fathers, sisters, and brothers of women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: PROSPERO 2016 CRD42016048551.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 89 publications
1
24
0
Order By: Relevance
“…Systolic, but not diastolic blood, pressure was significantly higher in male siblings of PCOS probands than in control men [ 5 , 6 ]. Men whose sisters were diagnosed with PCOS had increased levels of 2-h postchallenge glucose, were more insulin-resistant, more frequently met the criteria of metabolic syndrome [ 5 , 7 10 ], as well as were characterized by a higher prevalence of type 2 diabetes and impaired glucose tolerance than brothers of unaffected women [ 11 ]. They were also characterized by impaired brachial artery flow-mediated dilatation and this impairment was particularly pronounced in subjects with a family history of diabetes mellitus [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systolic, but not diastolic blood, pressure was significantly higher in male siblings of PCOS probands than in control men [ 5 , 6 ]. Men whose sisters were diagnosed with PCOS had increased levels of 2-h postchallenge glucose, were more insulin-resistant, more frequently met the criteria of metabolic syndrome [ 5 , 7 10 ], as well as were characterized by a higher prevalence of type 2 diabetes and impaired glucose tolerance than brothers of unaffected women [ 11 ]. They were also characterized by impaired brachial artery flow-mediated dilatation and this impairment was particularly pronounced in subjects with a family history of diabetes mellitus [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are not aware of previous studies regarding AGD in boys born of mothers with PCOS. However, previous studies regarding the male phenotype of PCOS reported that brothers of women with PCOS had higher levels of dehydroepiandrosterone sulfate and higher risk of dyslipidemia and insulin resistance compared to controls (Legro et al, 2002;Yilmaz et al, 2018). Furthermore, a recent study reported that PCOS offspring (boys and girls) had increased levels of inflammatory biomarkers, suggesting increased chronic low-grade inflammation (Daan et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…PCOS clusters within families and having a first degree relative suffering from PCOS conveys a 25% risk of either developing the full blown clinical picture or having a 25% risk of sharing characteristics of the syndrome amongst siblings to other siblings (6, 7). Similar results were obtained in several twin studies showing higher rates of concordance in PCOS characteristics between monozygotic twin sisters compared to dizygotic twins (8).…”
Section: Genetics Of Pcosmentioning
confidence: 99%